The Triad of Community Participation, Empowerment and Vigilance in Fraud Deterrence Strategy - Carolina, Anita; Bullah, Habi (Universitas Pendidikan Ganesha, 2024)
Fraud deterrence in the context of rural tourism poses specific difficulties and opportunities, particularly in environmentally sensitive places like mangrove tourism sites. This quantitative research investigated the critical relationship between community participation, community empowerment, and community vigilance, collectively forming the triad, in the context of fraud deterrence within four distinct mangrove tourism destinations in Madura, Indonesia. Through an extensive survey conducted among residents of these destinations, this study utilized structural equation modelling. By assessing the data on community participation, empowerment, vigilance, and anti-fraud measures, this research aims to unravel the complex web of relationships among these variables. The findings suggested that community participation and community vigilance contribute significantly to the success of fraud deterrence initiatives. Community empowerment, on the other hand, has no effect on fraud deterrence strategies due to several inherent factors in the community. These findings highlight the importance of engaging communities in decision-making processes and promoting vigilance to enhance transparency and accountability in tourism management. However, the lack of influence from community empowerment suggests that broader structural factors may hinder its effectiveness in fraud prevention. The study concludes that strengthening community participation and vigilance can play a critical role in preventing fraud and ensuring sustainable tourism development. Practical implications for tourism management and policymakers include the need to invest in community-driven fraud detection and reporting mechanisms.